Endocannabinoids Measurement in Human Saliva as Potential Biomarker of Obesity - Matias, Isabelle; Gatta-Cherifi, Blandine; Tabarin, Antoine; Clark, Samantha; Leste-Lasserre, Thierry; Marsicano, Giovanni; Piazza, Pier Vincenzo; Cota, Daniela (PLOS ONE, 2012)
Background The discovery of the endocannabinoid system and of its role in the regulation of energy balance has significantly advanced our understanding of the physiopathological mechanisms leading to obesity and type 2 diabetes. New knowledge on the role of this system in humans has been acquired by measuring blood endocannabinoids. Here we explored endocannabinoids and related N-acylethanolamines in saliva and verified their changes in relation to body weight status and in response to a meal or to body weight loss. Methodology/Principal Findings Fasting plasma and salivary endocannabinoids and N-acylethanolamines were measured through liquid mass spectrometry in 12 normal weight and 12 obese, insulin-resistant subjects. Salivary endocannabinoids and N-acylethanolamines were evaluated in the same cohort before and after the consumption of a meal. Changes in salivary endocannabinoids and N-acylethanolamines after body weight loss were investigated in a second group of 12 obese subjects following a 12-weeks lifestyle intervention program. The levels of mRNAs coding for enzymes regulating the metabolism of endocannabinoids, N-acylethanolamines and of cannabinoid type 1 (CB1) receptor, alongside endocannabinoids and N-acylethanolamines content, were assessed in human salivary glands. The endocannabinoids 2-arachidonoylglycerol (2-AG), N-arachidonoylethanolamide (anandamide, AEA), and the N-acylethanolamines (oleoylethanolamide, OEA and palmitoylethanolamide, PEA) were quantifiable in saliva and their levels were significantly higher in obese than in normal weight subjects. Fasting salivary AEA and OEA directly correlated with BMI, waist circumference and fasting insulin. Salivary endocannabinoids and N-acylethanolamines did not change in response to a meal. CB1 receptors, ligands and enzymes were expressed in the salivary glands. Finally, a body weight loss of 5.3% obtained after a 12-weeks lifestyle program significantly decreased salivary AEA levels. Conclusions/Significance Endocannabinoids and N-acylethanolamines are quantifiable in saliva and their levels correlate with obesity but not with feeding status. Body weight loss significantly decreases salivary AEA, which might represent a useful biomarker in obesity.